PENGARUH PROSES DAN BUKTI FISIK TERHADAP KEPUASAN KONSUMEN DI HOTEL SANTIKA BANDUNG - Iffan, Muhammad; Santy, Raeni Dwi; Radiaswara, Rengga (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
This research aimed at determining the impact of process and physical evidence on customer satisfaction. Methods used in this research was quantitative analysis using multiple regression analysis with validity and reliability test. Sampling method used in this research is random sampling through the distribution of a series of questionnaires to 93 customers at Santika Hotel as a case study. This research investigated process and physical evidence that affected customer satisfaction. The result showed that both variables have significant effect on customer satisfaction either partially or simultaneously.Keyword: Process, Physical Evidence, Customer Satisfaction